TRADISI “BUNGO LADO” SEBAGAI REPRESENTASI BUDAYA ISLAM DI KABUPATEN PADANG PARIAMAN - Andri Maijar (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2018)
Representation means using language to declare something meaningfully or present something to someone else. Representation can take the forms of word, picture, sequence, story and so on that represent idea, emotion, fact and etc. The development of tradition in a region is mainly found in various customary rituals or religious events. For Minangkabau-Malay people, their faith as Minangkabau people is the faith of homoreligious and basically it has been soldered in Minangkabau tambo that's traditionally become the guideline of their customary behavior. The tradition of Bungo Lado performed in the event of Prophet Muhammad's Birthday in Padang Pariaman is one of people's representations toward Islamic culture for society. Bungo lado, the flower of Chili, is  the decorative tree that its leaves made of money hence it' s called money tree. It is one of people's euphorias in welcoming the birthday of prophet Muhammad SAW. In its implementation, every group in society is competing one and another to donate half of their income by putting or decorating the money on the twigs of tree as the form of their happiness.